Factors associated with optic disc parameters and circumpapillary retinal nerve fiber layer thickness in 8-year-old children: The Yamanashi Adjunct Study of the Japan Environment and Children’s Study - Ryo Harada; Mingxue Bao; Natsuki Okabe; Yuka Kasai; Airi Takahashi; Chio Kuleshov; Yumi Shigemoto; Tadao Ooka; Hiroshi Yokomichi; Kunio Miyake; Reiji Kojima; Ryoji Shinohara; et al. (PLoS ONE, 2025)
Purpose The purpose of this study was to investigate the relationships between the circumpapillary retinal nerve fiber layer thickness (cpRNFL) and optic disc parameters and associated factors in 8-year-old Japanese children who participated in the Yamanashi Adjunct Study of the Japan Environment and Children’s Study (JECS). Subjects and methods The participants in this study were 559 8-year-old Japanese children (277 boys and 282 girls) who participated in the Yamanashi Adjunct Study of JECS at the University of Yamanashi from June 2021 to March 2022. The visual acuity, spherical equivalent (SE), and axial length (AL) of the participants were measured. The cpRNFL thickness was measured with a spectral domain optical coherence tomograph (NIDEK RS-3000 Advance, Gamagori, Japan). Results The data of 349 participants (182 boys and 167 girls) were ultimately analyzed. Multivariable analysis showed that AL was significantly positively correlated with the cpRNFL thickness in the 8 o’clock sector (β = 0.26; 95% confidence interval (CI) 2.74–6.87) and significantly negatively correlated with the cpRNFL thickness in the 6 o’clock sector (β = −0.21; 95%CI −9.94–-2.98). The cpRNFL thickness in the 10 o’clock and 11 o’clock sectors was greater for girls than for boys (β = 0.21; 95%CI 2.54–8.34; and β = 0.15; 95%CI 1.85–11.99, respectively), whereas in the 12 o’clock sector, it was greater for boys (β = −0.26; 95%CI −20.41–-8.32). The disc area was significantly positively correlated with the cpRNFL thickness in the 7 o’clock, 10 o’clock and 11 o’clock sectors (β = 0.13, 95%CI 0.93–8.67; β = 0.13, 95%CI 10.36–23.88; and β = 0.27, 95%CI 10.36–23.88, respectively). Conclusion The thickness of the cpRNFL in 8-year-old Japanese children was associated with AL, sex, and disc area, but these associations differed by RNFL sector.